2005
DOI: 10.1590/s0037-86822005000600005
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos epidemiológicos, clínicos e parasitológicos da doença de Chagas em Mato Grosso do Sul

Abstract: RESUMOCom o objetivo de avaliar aspectos epidemiológicos, clínicos e parasitológicos da doença de Chagas crônica, em pacientes do Hospital Universitário da Universidade Federal de Mato Grosso do Sul, realizamos um estudo seccional envolvendo 120 chagásicos e 120 controles não-chagásicos, de ambos os sexos, com idades de 16 a 82 anos. Os aspectos epidemiológicos foram avaliados por questionário, a cardiopatia por exame clínico, eletrocardiograma convencional, radiologia e ecodopplercardiograma e a presença de T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
(5 reference statements)
1
4
1
2
Order By: Relevance
“…CD positivity was 5 times higher among those who had only partially attended elementary school compared with those who completed elementary school. This result was also observed in previous studies, regardless of the region of the country 23,27,28,29 , indicating that a higher education level is associated with a lower CD prevalence.…”
Section: Discussionsupporting
confidence: 88%
“…CD positivity was 5 times higher among those who had only partially attended elementary school compared with those who completed elementary school. This result was also observed in previous studies, regardless of the region of the country 23,27,28,29 , indicating that a higher education level is associated with a lower CD prevalence.…”
Section: Discussionsupporting
confidence: 88%
“…The profile of seropositive individuals regarding education level revealed a predominance of individuals with low levels of education, suggesting that infection is closely related to the development of the population, generally affecting the poorest individuals and those with less education. Several authors have reported similar findings 6,26,32,34 , including one study characterizing illiteracy as the principal social marker of Chagas infection 23 .…”
Section: Ethical Considerationsmentioning
confidence: 62%
“…(VEXENAT et al, 1996;LUCIANO et al, 2009). In our study, cross-reactivity between dog serum samples positive to T. cruzi and L. braziliensis could not be discarded, since the occurrence of T. cruzi and L. braziliensis among dogs is documented in the state of Mato Grosso do Sul (POMPILIO et al, 2005;SAVANI et al, 2009;SOUZA et al, 2009;CORVALAN et al, 2011). One dog that tested positive in the Leishmania spp.…”
Section: Methodsmentioning
confidence: 94%